Avaliação do serviço de psicologia da assistência estudantil no Instituto Federal do Ceará - Oliveira, Raquel Campos Nepomuceno de (2017)
Even though School / Educational Psychology is an area that has been developed in Brazil for a long time, the work with Student Assistance in Higher Education is a relatively new field for psychologists. After the publication of the National Program for Student Assistance, the PNAES, in 2010, the Federal Government started to invest specific resources to meet the needs of students from Federal Institutions of Higher Education - IFES. Considering the scenario of the university expansion promoted by the Program of Expansion and Restructuring of Federal Universities - REUNI, there has been an increase in the number of available positions for administrative technicians. Between 2008 and 2012, almost 8,000 new administrative technicians were hired for the IFES, including the 27 psychology professionals working in the IFCE Student Assistance. The aim of this study is to evaluate how psychology works in these institutions, since it is a public policy that currently does not have its own institutionalized evaluation mechanisms. Based on the assumptions of the historical-cultural perspective, it is understood that it is essencial to modify the social structures, in order to expand the possibilities of construction of meanings, and, therefore, of subjectivation. In this sense, this study goes through the definition of what is public policy, to characterize the Student Assistance in this study field in brazilian scenario and, later, to evaluate to a model of execution of this policy in a Federal Institution of Higher Education. It is sought to emphasize the definition of the psychologist and the student's perspective regarding the performance of the psychologist in the institution, since the students are the final public of the actions. It is considered that this research represents a valuable contribution to the performance in the area of School / Educational Psychology and also for Student Assistance. It is proposed to establish an evaluation panorama of the psychologists’s work in Student Assistance, in order to contribute to the identification of needs that had not still been met, as well as the solidification of a culture of evaluation and planning of public policies for students’s assistance.